2019
DOI: 10.1101/gr.249789.119
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of polymerase III–transcribed Alu elements suggests cell-type–specific enhancer function

Abstract: Alu elements are one of the most successful families of transposons in the human genome. A portion of Alu elements is transcribed by RNA Pol III, whereas the remaining ones are part of Pol II transcripts. Because Alu elements are highly repetitive, it has been difficult to identify the Pol III-transcribed elements and quantify their expression levels. In this study, we generated high-resolution, long-genomic-span RAMPAGE data in 155 biosamples all with matching RNA-seq data and built an atlas of 17,249 Pol III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
76
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 54 publications
2
76
1
Order By: Relevance
“…Early studies have shown that RNAPIII is responsible for the transcription of small noncoding RNAs, such as transfer RNAs (tRNAs), 5S ribosomal RNA (rRNA), U6 small nuclear RNA, and 7SL RNA (RN7SL1 RNA) in eukaryotes (Paule and White, 2000;Geiduschek and Kassavetis, 2001;Dieci et al, 2007). These small noncoding RNAs play widespread roles in basic biological activities, including protein synthesis (tRNAs), ribosome biogenesis (5S rRNA; Ciganda and Williams, 2011), mRNA splicing (U6 small nuclear RNA), membrane targeting of newly translated proteins (7SL RNA; Dieci et al, 2002), and selective mRNA export (SINE RNAs; Ponicsan et al, 2010;Karijolich et al, 2017) and they also act as cell-type-specific enhancers (Alu elements; Hardeland and Hurt, 2006;Zhang et al, 2019). These findings suggest that RNA-PIII is required for growth, development, and reproduction (Goodfellow and White, 2007;Filer et al, 2017).…”
mentioning
confidence: 99%
“…Early studies have shown that RNAPIII is responsible for the transcription of small noncoding RNAs, such as transfer RNAs (tRNAs), 5S ribosomal RNA (rRNA), U6 small nuclear RNA, and 7SL RNA (RN7SL1 RNA) in eukaryotes (Paule and White, 2000;Geiduschek and Kassavetis, 2001;Dieci et al, 2007). These small noncoding RNAs play widespread roles in basic biological activities, including protein synthesis (tRNAs), ribosome biogenesis (5S rRNA; Ciganda and Williams, 2011), mRNA splicing (U6 small nuclear RNA), membrane targeting of newly translated proteins (7SL RNA; Dieci et al, 2002), and selective mRNA export (SINE RNAs; Ponicsan et al, 2010;Karijolich et al, 2017) and they also act as cell-type-specific enhancers (Alu elements; Hardeland and Hurt, 2006;Zhang et al, 2019). These findings suggest that RNA-PIII is required for growth, development, and reproduction (Goodfellow and White, 2007;Filer et al, 2017).…”
mentioning
confidence: 99%
“…In yeast RNA pol II transcriptional activity was demonstrated in the rDNA non-coding regions [52], and the pol II derived transcripts were shown to regulate nucleolar dynamics in higher eukaryotes [53]. In addition, the ribosomal intergenic spacer contains multiple Alu-repeats, evolutionarily originated from 7SL RNA genes [54], and may be potentially transcribed by RNA pol III [55]. We further plan to determine both the enzyme involved in the transcription of the non-coding RNAs detected in the current study and regulation of their expression.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed a link between Alu elements and the control of gene expression (Hanke et al, 1995;Mallona et al, 2016;Chen et al, 2018). Many of these findings came from extensive computational analyses of genome-wide epigenomic and transcriptomic data (Goerner-Potvin and Bourque, 2018;Zhang et al, 2019); however, the direct functional testing of Alu sequences and their contribution repeat to gene regulatory networks have remained poorly explored.…”
Section: Discussionmentioning
confidence: 99%